2004
DOI: 10.1163/22941932-90000377
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Vessel Characteristics in the Xylem of Ilex Paraguariensis (Maté-Tree) From South Brazil

Abstract: In this study the wood anatomy of two leaf-morphotypes (“Yellow” and “Grey”) of Ilex paraguariensis St. Hil. (Aquifoliaceae) from South Brazil was compared with special attention to vessel attributes and a possible relationship of leaf morphology and wood structure. Sampling was carried out in a 15-year-old plantation in the state of Paraná, South Brazil. The anatomy of the juvenile and mature wood of five male and five female plants of each morphotype was investigated by light microscopy. In all plants the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Since our studied seedlings were grown in the same plantation, observed differences in the anatomical characteristics of vessel elements during the juvenile phase of growth might be explained by genetic variation among seed sources. In agreement with our results, Dünisch et al (2004) reported a genetic control on the anatomical characteristics of vessel elements in two leaf-morphotypes of Ilex paraguariensis from south Brazil.…”
Section: Resultssupporting
confidence: 93%
“…Since our studied seedlings were grown in the same plantation, observed differences in the anatomical characteristics of vessel elements during the juvenile phase of growth might be explained by genetic variation among seed sources. In agreement with our results, Dünisch et al (2004) reported a genetic control on the anatomical characteristics of vessel elements in two leaf-morphotypes of Ilex paraguariensis from south Brazil.…”
Section: Resultssupporting
confidence: 93%
“…The values of the vessel diameter indicated an increase in the pith-bark direction. This tendency was also verified by Dünisch et al (2004), Chagas et al (2007), Roque and Tomazello Filho (2009) and Melo et al (2013). Carlquist (1989) reports that the increase in vessel diameter in the radial direction (pith-bark) as a function of the tree'sage can be considered an anatomical adaptation of the xylem to increase the sap volume, and to consequently increase its photosynthetic capacity.…”
Section: Speciementioning
confidence: 66%
“…The maximum diameter of vessels and tracheids tends to increase with cambial age (Fisher and Ewers 1995;Gartner et al 1997;Domec and Gartner 2002;Sperry et al 2006), although this was not true for holly oak (Quercus ilex L.) (Dünisch et al 2004). Maximum conduit size is limited by embolisms (Tyree et al 1994;Hacke and Sperry 2001;Gartner et al 2003).…”
Section: [Equation 1]mentioning
confidence: 99%